The Effect of Labor Comfort on Traumatic Childbirth Perception, Post-Traumatic Stress Disorder, and Breastfeeding - Turkmen, Hulya; Yalnız Dilcen, Hacer; Akin, Bihter; Dilcen, Hacer Yalnız (Mary Ann Liebert, Inc, 2020)
Objective:This study aims to examine the effect of labor comfort on traumatic childbirth perception, post-traumatic stress disorder (PTSD), and breastfeeding after the fourth postpartum week. Methods:This prospective longitudinal study was conducted between June 2019 and February 2020 in Turkey (n = 102). A personal information form and the Childbirth Comfort Questionnaire were administered to pregnant women with cervical dilatation of 5-8 cm in the delivery room. They were also administered the Traumatic Childbirth Perception Scale (TCPS), PTSD Scale, and Breastfeeding Self-Efficacy Scale twice, including 4 weeks and 3 months after childbirth. Additionally, the TCPS and PTSD Scale were reapplied 6 months after childbirth. Results:The prevalence of traumatic childbirth perceptions and PTSD at 4 weeks of the postpartum period was 68.6% and 59.8%, respectively. The multiple linear regression analysis revealed a significant relationship between physical labor comfort (p = 0.003), transcendence (p = 0.023), family history of labor difficulty (p = 0.027), and feelings about birth before labor begins (p = 0.005) and traumatic childbirth perceptions 4 weeks after childbirth. Additionally, there was a significant relationship between physical labor comfort (p = 0.001), psychospiritual labor comfort (p = 0.006), transcendence (p = 0.001), primiparity (p = 0.009), place of residence (p = 0.044), and traumatic childbirth perceptions (p < 0.001) and PTSD 4 weeks after childbirth. Physical labor comfort affected traumatic childbirth perceptions 3 and 6 months after childbirth (p < 0.05). Physical labor comfort affected breastfeeding self-efficacy 4 weeks and 3 months after childbirth (p < 0.05). A significant relationship was also found between high traumatic childbirth perception levels, high PTSD prevalence, and low breastfeeding self-efficacy 3 months after giving birth (p < 0.05). Conclusions:Puerperal women had high traumatic childbirth perception levels and PTSD prevalence. Low labor comfort increased traumatic childbirth perception and PTSD prevalence. There was a significant relationship between low labor comfort, high traumatic childbirth perception level, high PTSD prevalence, and low breastfeeding self-efficacy. Therefore, midwives should support pregnant women to increase labor comfort by using alternative methods. Thus, traumatic childbirth perception may decrease and breastfeeding self-efficacy may increase.
Keywords: Labor Comfort; Traumatic Childbirth Perception; Post-Traumatic Stress Disorder; Breastfeeding Self-Efficacy